Cross-linking of acrylate pressure sensitive adhesives dispersions - Czech, Z. (Polimery, 2022)
This review presents general characteristics of water-based crylate pressure sensitive adhesive dispersions (properties, pplications, monomers used for synthesis). Detailed discussion as been given of cross-linking processes of such adhesivesusing chemical agents (unsaturated monomers, monomers with unctional groups, other non-acryl monomers, multifunctional ropyleneimines, metal acetylacetonates and organic acid alts). Cross-linking of pressure sensitive adhesives under UV adiation was also discussed, concentrating mainly on the types f radical photoinitiator types used (conventional orunsaturated - capable of participating in the polymerization), s well as photoinitiators capable of participating in the ddition process. UV sources were described, with special ttention to excimer lasers.